2004
DOI: 10.1016/j.jvs.2003.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasound scan findings two years after great saphenous vein radiofrequency endovenous obliteration

Abstract: RFO is the ideological opposite of high ligation without GSV stripping. It leaves physiologic tributary flow relatively undisturbed, does not incite groin neovascularity, eliminates the GSV as a refluxing conduit in >90% of limbs and has a 2-year, postadjunctive phlebectomy varicosity prevalence of 7.9%, with symptom score improvement in 95% of limbs with an initial score higher than zero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 17 publications
9
106
0
2
Order By: Relevance
“…The lower incidence of neovascularization with RFA was also reported by Pichot and colleagues [29]. Sixty three limbs were studied with ultrasound scan protocol and found to have no evidence of neovascularization at 2 years after the treatment.…”
Section: Endovenous Radiofrequency Ablation Versus Vein Strippingsupporting
confidence: 71%
See 2 more Smart Citations
“…The lower incidence of neovascularization with RFA was also reported by Pichot and colleagues [29]. Sixty three limbs were studied with ultrasound scan protocol and found to have no evidence of neovascularization at 2 years after the treatment.…”
Section: Endovenous Radiofrequency Ablation Versus Vein Strippingsupporting
confidence: 71%
“…Four types of SFJ morphologies were identified [25,28,29]. The three most common include: J-1, defined as complete SFJ obliteration with no SFJ flow; J-2 as patent SFJ tributaries draining toward the femoral vein with or without a short saphenous stump; and J-3 as terminal GSV competence with normal antegrade flow coming from both tributaries and the saphenous vein above a limited GSV obliteration.…”
Section: Treatment Efficacy and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] Thus, the inconsistency noted above might be explained by the hypothesis that performing SFJ ligation not only leads to less incompetent groin tributaries but also augments neovascularization in the groin.…”
Section: S Uperficial Venous Insufficiency Is a Common Medicalmentioning
confidence: 99%
“…12 Although, following treatment with radiofrequency ablation of great saphenous vein, there should not be any remnant flow, many studies have found limited reflux in some segments of treated GSV. 13,14 This failure of occlusion, shrinkage and disappearance of the treated segment of vein can be due to a fact that the heating segment may not adequately touch the vein wall throughout the length. This can happen if there is inadequate instillation of perivenous fluids.…”
mentioning
confidence: 99%